2010
DOI: 10.1093/nar/gkq184
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide assessment of differential roles for p300 and CBP in transcription regulation

Abstract: Despite high levels of homology, transcription coactivators p300 and CREB binding protein (CBP) are both indispensable during embryogenesis. They are largely known to regulate the same genes. To identify genes preferentially regulated by p300 or CBP, we performed an extensive genome-wide survey using the ChIP-seq on cell-cycle synchronized cells. We found that 57% of the tags were within genes or proximal promoters, with an overall preference for binding to transcription start and end sites. The heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
143
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 55 publications
4
143
0
Order By: Relevance
“…Other investigators have also observed a critical role for p300 in ADI prostate cancer cells (6). In addition, a genome-wide ChIP analysis of p300 and CBP in glioblastoma cells revealed that the majority of genes that were regulated by serum addition were bound preferentially by p300 rather than CBP (39).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Other investigators have also observed a critical role for p300 in ADI prostate cancer cells (6). In addition, a genome-wide ChIP analysis of p300 and CBP in glioblastoma cells revealed that the majority of genes that were regulated by serum addition were bound preferentially by p300 rather than CBP (39).…”
Section: Discussionmentioning
confidence: 86%
“…Although the differential requirement for p300 in this case was not due to differential recruitment of p300, the mechanism responsible for the differential requirement presumably lies in some different aspect of promoter environment at the two genes. As suggested by Ramos et al (39), differences in binding sites for other transcription factors near the ARE could influence whether p300 or CBP is recruited. In addition, differences in the DNA sequence at steroid receptor binding sites can lead to altered conformations of the DNAbound steroid receptor, resulting in recruitment of different sets of coactivators (40 -43).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this paper, we use for illustration the ChIP-Seq data generated by Ramos et al (2010) for identifying the genomic regions bound by the histone acetyltransferases p300.…”
Section: Poisson or Negative Binomial Distributions)mentioning
confidence: 99%
“…Table 1 provides the summary statistics for the data set, where we consider only the data for 1000bp windows along chromosome 21 (Bao et al, 2013). Figure 1 shows Ramos et al (2010) for one experiment on the protein p300 on chromosome21.…”
Section: Poisson or Negative Binomial Distributions)mentioning
confidence: 99%